2024
DOI: 10.3390/sports12040100
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Coach-Created Empowering and Disempowering Climate Effects on Athletes’ Intentions to Use Doping: The Mediational Role of Self-Regulatory Efficacy and Attitudes towards Doping

Beatrice Hoppen,
Saulius Sukys

Abstract: Background: The purpose of this study was to examine the relationship between perceived coach-created empowering and disempowering motivational climate and doping likelihood among athletes and whether the attitudes towards doping and doping self-regulatory efficacy mediates these relationships. Methods: Athletes (N = 948; 50% male; mean age, 20.32, SD = 2.45) recruited from a variety of sports completed questionnaires assessing their perceptions of coach-created motivational climate, attitudes towards doping, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
(86 reference statements)
1
2
0
Order By: Relevance
“…Moreover, the findings revealed that mastery climate was negatively associated with doping attitudes, while a performancefocused climate was positively correlated with doping attitudes. This findings aligns with previous studies that have found athletes high in mastery climate and low in performance climate associated with negative attitudes towards doping and performance climates with positive doping attitudes (Allen et al, 2015;Bae et al, 2017;Hoppen & Sukys, 2024).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the findings revealed that mastery climate was negatively associated with doping attitudes, while a performancefocused climate was positively correlated with doping attitudes. This findings aligns with previous studies that have found athletes high in mastery climate and low in performance climate associated with negative attitudes towards doping and performance climates with positive doping attitudes (Allen et al, 2015;Bae et al, 2017;Hoppen & Sukys, 2024).…”
Section: Discussionsupporting
confidence: 92%
“…Motivational climate refers to the situational goal structure affecting athletes’ task and ego involvement in sports (Ames, 1992). Coaches play a significant role in creating the motivational climate for athletes (Allen et al, 2015;Hoppen & Sukys, 2024;Newton et al, 2000). Coach created mastery climate emphasizes on cooperation, personal improvement, and effort, while performance climate emphasizes competition, intra-team rivalry, punishment for mistakes, unequal recognition of athletes, and winning at all costs (Newton et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation